A novel antioxidant peptide, purified from Bacillus amyloliquefaciens, showed strong antioxidant potential via Nrf-2 mediated heme oxygenase-1 expression. (15th January 2018) - Rahman, Md. Saifur; Hee Choi, Yun; Seok Choi, Yoon; Alam, Md. Badrul; Han Lee, Sang; Cheol Yoo, Jin
Highlights: A novel glycine-rich antioxidant peptide purified from Bacillus amyloliquefaciens. Showed antioxidant potential via Nrf-2 mediated heme oxygenase-1 expression. YD1 displayed active against gram-positive, negative and resistant bacteria. Abstract: A novel antioxidant peptide YD1 (∼1.0 kDa), purified from the strain Bacillus amyloliquefaciens CBSYD1, displayed activity in several in vitro assays and was also efficient against Gram-positive, Gram-negative as well as multidrug-resistant (MDR) bacteria. Strain growth was adapted to bile-salt conditions where a clear halos-zone was observed in a bile-salt plate assay and was viable in different digestive track conditions. YD1 treatment on RAW 264.7 cells increased the transcriptional and translational activities of NF-E2-related factor-2 (Nrf-2) through the enhanced levels of heme oxygenase-1 (HO-1). Furthermore, the YD1-treated group showed higher levels of antioxidant enzymes compared to the oxidative stress group. YD1 demonstrated a strong antioxidant activity by decreasing nitric oxide (NO) and reactive oxygen species (ROS) in RAW 264.7 cells. This study suggests that YD1 and the strain could be a natural antioxidant and a probiotic candidate respectively.